2010
DOI: 10.1590/s0103-21002010000600019
|View full text |Cite
|
Sign up to set email alerts
|

O processo de recuperação da criança após a alta hospitalar: revisão integrativa

Abstract: Objective: To identify the available knowledge about the process of recovery of hospitalized children and their families after discharge. Methods: Integrative review of literature in databases -national and international -with a qualitative approach. Results: The 16 selected articles belonging to international journals were published between 1990 and 2005; they allowed the identification of the following topics: biopsychosocial manifestations of the child and his family; Biopsychosocial factors related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(70 reference statements)
1
2
0
3
Order By: Relevance
“…Junior staff found providing transition information challenging due to their limited experience and lack of standardization of the information, as identified previously (Chidume & Pass-Ivy, 2019). Study findings confirmed those of earlier studies in that information provided at discharge was too generalized for some caregivers (Keatinge et al, 2009;Pinto et al, 2010Pinto et al, , 2015. Caregivers in this study also identified unmet information needs, such as what signs and symptoms to expect and duration of recovery and this impacted caregivers' perceptions of whether they felt ready for discharge (Lerret et al, 2014(Lerret et al, , 2015Solan et al, 2015;Weiss et al, 2017).…”
Section: Discussionsupporting
confidence: 75%
“…Junior staff found providing transition information challenging due to their limited experience and lack of standardization of the information, as identified previously (Chidume & Pass-Ivy, 2019). Study findings confirmed those of earlier studies in that information provided at discharge was too generalized for some caregivers (Keatinge et al, 2009;Pinto et al, 2010Pinto et al, , 2015. Caregivers in this study also identified unmet information needs, such as what signs and symptoms to expect and duration of recovery and this impacted caregivers' perceptions of whether they felt ready for discharge (Lerret et al, 2014(Lerret et al, , 2015Solan et al, 2015;Weiss et al, 2017).…”
Section: Discussionsupporting
confidence: 75%
“…In this sense, discharge planning together with the family and home visits for monitoring represent an important support source, involving informa on, individualized care and permanent monitoring, minimizing feelings of anxiety and fear (18) . Despite a signifi cant change in family dynamics, the nursing orienta ons provided throughout the hospitaliza on period and upon discharge were essen al to construct this mother's autonomy for care delivery to her child, facilita ng care con nuity at home.…”
Section: Discussionmentioning
confidence: 99%
“…Para tanto, a enfermagem pode tornar-se uma aliada a partir do compartilhamento entre seus saberes técnico-científicos e os conhecimentos advindos do saber popular dos cuidadores, contribuindo para o bem-estar da criança, evitando complicações e reinternações frequentes 8 . A alta planejada conjuntamente com a família e a visita domiciliar de acompanhamento tornam-se uma importante fonte de apoio, por meio de informações, atenção individualizada e seguimento contínuo, minimizando os sentimentos de ansiedade e medo 24 . Nessa perspectiva, faz-se necessário ampliar a visibilidade dessa clientela nas taxas oficiais e nas políticas públicas por meio da ampliação e aprofundamento de estudos desta natureza, os quais podem se constituir em subsídios para pensar o processo de cuidado às crianças com necessidades especiais de saúde e suas famílias.…”
Section: Discussionunclassified